Scrotal abscess with xanthogranulomatous epididymo-orchitis: a case report of rare diagnostic entity - Dr. Renuka Verma; Dr. Niti Dalal; Dr. Archana Yadav; Dr. Richa Pawar; Dr. Sunita Singh (Tropical Journal of Pathology and Microbiology, 2020)
Xanthogranulomatous epididymo-orchitis is an extremely rare diagnostic entity presenting as a scrotal mass with or without pain. Rarely, it can affect prostate, epididymis, and testicle. It can mimic a testicular malignancy both clinically as well as radiologically, hence, careful pathological examination and biomarker study are essential to rule out malignancy. We report a case of 50 years old male with increasing right testicular swelling with a discharging pus. Skin over scrotum was gangrenous. Right orchidectomy was performed. Histopathological diagnosis revealed features of xanthogranulomatous epididymo-orchitis with no evidence of malignancy. IHC markers for tumor were negative.